2001
DOI: 10.1016/s0378-1135(01)00354-6
|View full text |Cite
|
Sign up to set email alerts
|

Deletions in the 7a ORF of feline coronavirus associated with an epidemic of feline infectious peritonitis

Abstract: A population of Persian cats experienced an epidemic of feline infectious peritonitis (FIP) over 2 years. Twelve cases of FIP occurred in litters born during this period. Cats contracting FIP were all genetically related through the sire. Feline coronavirus (FCoV) genomic RNA was detected consistently in this study in biologic samples from adult cats, kittens suffering from FIP, and their siblings. Analysis of viral 7a/7b open reading frame (ORFs) were analyzed and revealed two distinct virus variants circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 8 publications
0
71
1
2
Order By: Relevance
“…Several genes, including the spike gene and the so-called group-specific genes 3c, 7a and 7b, have been suggested to be associated with the pathotypic switch (Kennedy et al, 2001;Rottier et al, 2005;Vennema et al, 1998). In particular, it has been noted that FIPV strains frequently carry mutations that inactivate the gene for 3c (Pedersen, 2009;Vennema et al, 1998), an accessory triple-spanning membrane protein with a predicted topology similar to that of SARS coronavirus 3a (Oostra et al, 2006).…”
mentioning
confidence: 99%
“…Several genes, including the spike gene and the so-called group-specific genes 3c, 7a and 7b, have been suggested to be associated with the pathotypic switch (Kennedy et al, 2001;Rottier et al, 2005;Vennema et al, 1998). In particular, it has been noted that FIPV strains frequently carry mutations that inactivate the gene for 3c (Pedersen, 2009;Vennema et al, 1998), an accessory triple-spanning membrane protein with a predicted topology similar to that of SARS coronavirus 3a (Oostra et al, 2006).…”
mentioning
confidence: 99%
“…Its function, however, is not clear. In FIPV, several studies have reported that deletion of ORF 7 correlates with the virulence of the virus [5,7].…”
mentioning
confidence: 99%
“…Further molecular studies are thus worth undertaking to disclose these molecular characteristics because viral molecular changes associated with FIP disease remains a very challenging question. 19,32 Our results showed that in the 15 cats presenting the typical clinical and pathologic picture of the dry form of FIP, CCV2-2 positivity in macrophages was always detected in lesions with MAC 387-positive cells. Thus, 46 of 49 samples stained positive with the CCV2-2 mAb, yielding a sensitivity of 94% for this mAb.…”
Section: Discussionmentioning
confidence: 59%